ANALISIS STABILITAS DINDING PENAHAN TANAH PLAZA ANDRAWINA, KOMPLEK SITUS RATU BOKO, YOGYAKARTA - , HANINDRA NUGRAHA; , Dr. Ir. Ahmad Rifaâi, M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia is a country with a very high probability of landslide. Besides the hilly topography, land use conditions in Indonesia also led the slopes in most areas become prone to move. Ratu Boko Temple site is built on steep hills, so it is possible if the slope instability occur in the region of Ratu Boko temple site. The unstable slope will affect the existing buildings surrounds the temple, including the retaining walls. This research aims to determine the safety factor of those slopes. The research method begins with secondary data collection and hand boring test. The data were interpreted before it can be use for further analysis. On the slopes, there are 9 retaining wall structures. In this analysis, each retaining wall structure named â1â for the retaining walls at the top, up to, â9â for the retaining wall at the bottom. Analysis of slope stability and retaining wall was conducted using the limit equilibrium method with Geostudio 2004 Slope / W Analysis. From this research, bottom width dimension (B) from each retaining wall that has been reviewed did not fulfil the dimensional requirements, required by Bowles (1971). In the static load analysis, the safety factor of overturn and sliding stability of retaining walls No. 6, 7, and 8 already fulfiled the requirements. The safety factors of retaining wall No. 9 for overturn stability and sliding does not fulfil the required safety factor. With the placement of counterfort structure, the sliding safety factor rise from 1,2 to 1,84 (counterfort part) and 1,79 (landfill part), the overturn safety factor also rise from 0,99 to 2,497 (counterfort part) and 2,369 (landfill part). Furthermore, these retaining walls has met the requirements of the soil bearing capacity. The lowest safety factor that obtained from the numerical simulation using Geostudio 2004 Slope / W Analysis program was occured on the slopes or on the retaining wall No. 9 by 1.02, which is collapse most likely to occur.